2021
DOI: 10.3389/fcimb.2021.703259
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epstein-Barr Virus and Human Papillomavirus Coinfection in Cervical Intraepithelial Neoplasia in Chinese Women Living With HIV

Abstract: Given that only a small percentage of human papillomavirus (HPV)-positive women develop cancer, HPV is necessary but insufficient for carcinogenesis. Mucosally transmitted viral cofactors appear to contribute to HPV-related cervical cancer, such as Epstein-Barr virus (EBV), but previous studies have shown inconsistent outcomes. The exact role of EBV in cervical cancer remains unclear, and more studies are needed to determine its involvement. In this study, we describe the prevalence of EBV and HPV coinfection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…Feng et al studied HIV+ Chinese women and found that women who were HPV/EBV positive had a higher incidence of high-grade cervical intraepithelial neoplasia. 23 It should be noted that HIV infection may increase the incidence of HPV/EBV coinfection and HPV-related malignancies due to compromised cellular immunity. In a study of Iranian women, Joharinia et al reported similar trends.…”
Section: Many Groups Investigating the Relationship Between Hpv Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng et al studied HIV+ Chinese women and found that women who were HPV/EBV positive had a higher incidence of high-grade cervical intraepithelial neoplasia. 23 It should be noted that HIV infection may increase the incidence of HPV/EBV coinfection and HPV-related malignancies due to compromised cellular immunity. In a study of Iranian women, Joharinia et al reported similar trends.…”
Section: Many Groups Investigating the Relationship Between Hpv Andmentioning
confidence: 99%
“…This group then looked at a new cohort of 295 HIV+ women, and they found that hrHPV infection alone did not significantly correspond to SIL incidence, but dual hrHPV/EBV positivity once again showed high association with SIL (~fourfolds increase from hrHPV+ alone). Feng et al studied HIV+ Chinese women and found that women who were HPV/EBV positive had a higher incidence of high‐grade cervical intraepithelial neoplasia 23 . It should be noted that HIV infection may increase the incidence of HPV/EBV coinfection and HPV‐related malignancies due to compromised cellular immunity.…”
Section: Ebv and Hpvmentioning
confidence: 99%
“…The vIL‐10 inhibits IFN‐γ, IL‐2, IL‐6, TNF‐α, and granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) production by CD4 + T lymphocytes and monocytes resulting in immune evasion of infected epithelial cells 104 . vIL‐10 impairs monocyte maturation and host natural defense system against viral infections 113 . IL‐10 induced by HPV E2, E6, and E7 proteins and vIL‐10 activate Janus kinase/STAT3 cascade that leads to reduction of TNF‐α, IL‐6, and IL‐1β expression interfering with the NF‐κB signaling pathway with increased tumorigenic and metastatic ability and epithelial‐mesenchymal transition (EMT) 111,114 .…”
Section: Co‐infection Of Hpvs With Other Virusesmentioning
confidence: 99%
“…It still remains to be explored whether the coinfection is the etiology or just a phenomenon which is not causality. HPV/EBV coinfection was reported to present in some of prostate cancer (PCa) cases ( Nahand et al., 2021 ), oral carcinogenesis ( Blanco et al., 2021 ), cervical cancer ( Feng et al., 2021 ), breast cancer ( Nagi et al., 2021 ), and nasopharyngeal carcinoma (NPC) ( Blanco et al., 2021 ) (shown in Table 1 ). The cytokine expression profile of PCa cases with HPV and EBV coinfection was quite different from that only infected with HPV or EBV.…”
Section: Implication Of Diverse Microbial Interacts With Ebv In Ebv-d...mentioning
confidence: 99%